Enterprise-Based Empowerment Strategy for Santri in the Agribusiness Sector in Creating an Influential (Infa’) Generation - Achmad Zam Zami; Sofuan Jauhari (Musyarakah: Journal of Sharia Economic (MJSE), 2026)
Public skepticism about the relevance of Islamic boarding school graduates in the modern job market creates a gap between the traditional curriculum and the demands of economic independence. An applied educational transformation is urgently needed so that students become not only religious figures but also strong economic actors. This study aims to analyze strategies for empowering students based on agribusiness entrepreneurship and describe the profile of the "Influential Santri Generation" as an output of the integration of economic independence and da'wah values at the Fathul Ulum Islamic Boarding School, Jombang. This study uses a qualitative approach with a field case study type. The study was conducted for six months, from January to June 2025, located at the agribusiness business unit of the Fathul Ulum Islamic Boarding School, Jombang. Data were collected from 25 respondents consisting of boarding school caretakers, business unit managers, and active students through in-depth interviews, participatory observation, and documentation studies. Data analysis was carried out inductively through data reduction, presentation, and verification. The results show that empowerment is carried out through systemic agribusiness technical training and strengthening business units with a fair profit-sharing model. Despite successfully improving practical competency and independent character, the study identified significant obstacles in the form of conventional business management and low digital technology literacy. However, this model has proven effective in forming a "Generation of Infa' Santri" who are economically competitive without abandoning their spiritual identity.